2019
DOI: 10.1002/oby.22616
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage‐Derived microRNA‐155 Increases in Obesity and Influences Adipocyte Metabolism by Targeting Peroxisome Proliferator‐Activated Receptor Gamma

Abstract: Objective This study aimed to investigate cellular sources of microRNAs (miRNA) within adipose tissue and the impact of obesity on miRNA expression, as well as to examine targets of miRNAs. Methods miRNA expression by quantitative polymerase chain reaction was examined in adipocytes, adipose tissue macrophages (ATM), and peripheral blood mononuclear cells from and individuals with normal weight and with obesity. Differentiated 3T3‐L1 adipocytes were cocultured with macrophages, and 3T3‐L1 and differentiated hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 40 publications
0
29
0
Order By: Relevance
“…In addition, researchers discovered that Mφs in adipose tissue can transport miRNAs through exosomes which finally influence the insulin sensitivity and glucose homeostasis (Ying et al, 2017). Evidence also confirmed that Mφ-derived microRNA can influence adipocyte metabolism (Tryggestad et al, 2019). These all indicate that Mφ-derived exosomes may also participate in the adipogenic differentiation of MSCs.…”
Section: Discussionmentioning
confidence: 91%
“…In addition, researchers discovered that Mφs in adipose tissue can transport miRNAs through exosomes which finally influence the insulin sensitivity and glucose homeostasis (Ying et al, 2017). Evidence also confirmed that Mφ-derived microRNA can influence adipocyte metabolism (Tryggestad et al, 2019). These all indicate that Mφ-derived exosomes may also participate in the adipogenic differentiation of MSCs.…”
Section: Discussionmentioning
confidence: 91%
“…Another miR-155 is overexpressed in obese ATMs and targets peroxisome proliferator-activated receptors (PPARγ). These miRs enter in insulin-secreting pancreatic islets of β cells through endocrine or paracrine regulation via robust effects on cellular insulin action to maintain glucose homeostasis [ 90 ]. miR-34a is identified as a vital mediator and attack on adipose-resident M2 macrophage to stimulate obesity and chronic inflammation [ 91 ].…”
Section: Mirs As a Bridge Between Adipocytes And At Macrophagesmentioning
confidence: 99%
“…Among all body fluids, HM is one of the richest sources of miRNAs [ 11 ]. These small, non-coding RNAs bind to complementary sequences within the 3′ untranslated region of messenger RNAs (mRNAs) and thereby modulate protein production, typically by degrading or repressing translation of targeted mRNAs [ 12 , 13 , 14 , 15 ]. They have been shown to function in multiple biological processes, including pathways involved in adipocyte differentiation, insulin signaling, and glucose metabolism [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%